„Kicz, kiczyzm” Justyny Bargielskiej - Lisak-Gębala, Dobrawa (Przestrzenie Teorii, 2019)
The article develops the analysis of recurrent kitschy motifs in poetry and prose by Justyna Bargielska. This authoress consciously and intensively takes advantage of pop-cultural kitsch, kitsch connected to maternity and femininity, sacrokitsch and consolatory kitsch used in mourning practices. She derives many fetishized objects from these areas and transforms them into private talismans; she also borrows many established pop-cultural visions that serve her heroines to create their identity, but sometimes these patterns become a costume for individual fears and phantasies. The term ‘kitschism’ was invented by Bargielska herself and it suggests intellectual distance towards the figures and requisites used. The writer’s attitude towards kitschy cliches is developed as a dialectical movement of attraction and repulsion, and is not meant to overthrow dominant stereotypes; this approach is often similar to camp strategies, yet it extends beyond ludic or ironic games. Bargielska is interested mainly in the anthropological aspect of kitsch, which is situated between the individual and the community. The writer tests the usefulness of cliches while confronting her heroines with the most serious subjects, like death, love or loss.